AL- MAUDUDI ON ISLAM AS BASIC IN INDIVIDUAL AND STATE LIFE ( Thought And Modernization Effort ) - Wisyly Wisyly (Universitas Islam Negeri Imam Bonjol Padang, 2017)
Abul A’la al-Maududi is one of Islamic renovators in India- Pakistan by his effort makes Islam as basic and identity for man life individually and has a state. An interesting one from al- Maududi is his consistency and ability to join and compose all his modernization thought becomes an integrating system that based on Islam. He offers consistently that Islam is as alternative and basic of life. Especially, Islamic political teory which built by al- Maududi in Pakistan is impressed an unique one. The uniqueness of that political teory is located in basic concept which confirms that sovereignty is in power of God not in power of man. With his idea in political teory, al- Maududi took over West modern sovereignty concept and said that sovereignty is just in power of God